BIOCHEMICAL INDICES OF ORAL FLUID AS MARKERS FOR THE FEATURES OF THE STRUCTURAL AND FUNCTIONAL STATE OF THE STOMATOGNATIC SYSTEM IN PERSONS WHO WERE BORN WITH MACROSOMIA - O.V. Garmash (Український стоматологічний альманах)
Two hundred sixty eight people in the Kharkiv and surrounding Provinces' population have been examined: one hundred sixty eight persons were born with macrosomia, and fifty persons were born with weight and height parameters that correspond to the norm. The macrosomic-at-birth persons were divided into groups, with allowance for the features of their intrauterine development.